The Role of Teacher Communication in Mathematics Learning: A Literature Review - M Mursalin; Mutia Fonna; M Muliana; Muhammad Ali; S Setiawan; Desi Armita (Electronic Journal of Education, Social Economics and Technology, 2025)
Teacher communication plays an important role in the effectiveness of mathematics learning, especially in helping students understand abstract concepts. This study aims to analyze the role of teacher communication in improving students' understanding and motivation in mathematics learning. The method used is a literature review by analyzing various studies that discuss teacher communication in the context of mathematics education. The results of the study show that effective communication allows teachers to create an inclusive learning environment, increase student interaction, and build higher learning motivation. Verbal and nonverbal communication, the use of technology in teaching, and interpersonal communication strategies have been proven to have a positive impact on students' understanding of concepts and participation in learning. The implications of these findings emphasize the importance of communication training for mathematics teachers to optimize interaction with students. The recommendations given include the development of technology-based communication strategies, the application of more interactive communication methods, and the improvement of teachers' communication skills through continuous training.